2019
DOI: 10.1177/0017896919886599
|View full text |Cite
|
Sign up to set email alerts
|

Environmental competencies for healthcare educators and trainees: A scoping review

Abstract: Background: The health-care community has a responsibility to address the environmental impact of delivering health-care services. Educational programmes present ideal fora to confer ‘environmental competencies’ to future health system leaders, managers, practitioners and researchers. The aim of this review is to synthesise the literature on health-care competencies, education and training of relevance to issues of environmental sustainability and climate change in the health sector. Methods: We conducted a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…A recent scoping review identified three core healthcare competencies as being specific to the environment, namely resource stewardship, systems thinking and social and environmental justice (Parker et al 2020). The American Association of Colleges of Nursing has taken steps to increase student and faculty awareness of all of the latter three competencies by enhancing curricula at undergraduate and graduate levels (Butterfield et al 2014), and in public health there is growing expectation that this content on environmental sustainability should be integrated into all university courses (Patrick et al 2016).…”
Section: Esh Learning Outcomes For Students and Facultymentioning
confidence: 99%
“…A recent scoping review identified three core healthcare competencies as being specific to the environment, namely resource stewardship, systems thinking and social and environmental justice (Parker et al 2020). The American Association of Colleges of Nursing has taken steps to increase student and faculty awareness of all of the latter three competencies by enhancing curricula at undergraduate and graduate levels (Butterfield et al 2014), and in public health there is growing expectation that this content on environmental sustainability should be integrated into all university courses (Patrick et al 2016).…”
Section: Esh Learning Outcomes For Students and Facultymentioning
confidence: 99%
“…communication, professionalism, leadership, and advocacy (Thistlethwaite and Moran 2010). Essential environmental competencies for healthcare educators and trainees include leadership, research skills, resource stewardship, systems thinking, social, environmental and ecological justice, and global citizenship (Parker et al 2020). Ethical codes, such as the International Council of Nurse's ethical codes for Nurses, provide a strong argument for a transdisciplinary approach to ESH, with the inclusion of beneficence and justice principles.…”
Section: Opportunities and Challengesmentioning
confidence: 99%
“…9 10 A recent scoping review found that environmental competencies within nursing, medicine and pharmacy fit in well with previously validated healthcare competencies of resource stewardship, systems thinking, and social and environmental justice. 11 …”
Section: Introductionmentioning
confidence: 99%
“…As a first step towards incorporating a planetary health curriculum within medical education, organisations such as the Health and Environment Adaptive Response Taskforce (HEART) have created a set of planetary health competencies to provide a framework for subsequent curricular development 9 10. A recent scoping review found that environmental competencies within nursing, medicine and pharmacy fit in well with previously validated healthcare competencies of resource stewardship, systems thinking, and social and environmental justice 11…”
Section: Introductionmentioning
confidence: 99%